CO32 | Major surgery in patients with severe hemophilia A without inhibitors receiving prophylaxis with fitusiran (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Fitusiran is an RNA interference therapy that lowers antithrombin (AT) levels, thereby restoring hemostatic balance in patients with hemophilia A or B, regardless of inhibitor status. However, clinical experience with perioperative management of major surgery in patients receiving fitusiran is still limited. We report three major surgical procedures performed in two patients with severe hemophilia A without inhibitors, treated with fitusiran, focusing on coagulation parameters and clinical outcomes.